Characterization of aroma compositions in different Chinese congou black teas using GC–MS and GC–O combined with partial least squares regression - Xiao, Zuobing; Wang, Hongling; Niu, Yunwei; Liu, Qiang; Zhu, Jiancai; Chen, Hexing; Ma, Ning (Flavour and fragrance journal, 2017)
To characterise the volatile aroma compositions of Chinese congou black teas, four types were analysed by quantitative descriptive sensory analysis, gas chromatography–mass spectrometry (GC–MS) and gas chromatography–olfactometry (GC–O). The aroma of Chinese congou black tea was described using six sensory terms: ‘Roasted’, ‘Sweet’, ‘Malty’, ‘Green grassy’, ‘Floral’ and ‘Woody’. A total of 64 compounds including alcohols (20), aldehydes (12), ketones (12), esters and lactones (9), pyrazines (7) and other compounds (4) were identified and quantified in four Chinese black tea samples. The highest amount of volatile aroma compounds was found in Tanyang congou black tea (TY) (29.8 mg/kg), followed by Dianhong congou black tea (DH) (29.4 mg/kg), Keemun congou black tea (KM) (24.1 mg/kg) and Yixing congou black tea (YH) (23.6 mg/kg). Through aroma extract dilution analysis (AEDA) on the black tea extract, the flavour dilution factor (FD factor) ranged from 41 to 46. Trans‐linalool oxide in DH, geraniol in TY, DH and KM were identified with the highest flavour dilution (FD = 4096) factors. The relationship between tea samples, sensory attributes and aroma‐active compounds was modelled by partial least squares regression (PLSR), and the PLSR analysis revealed that pentanal showed a significant and positive correlation with the ‘Malty’ attribute, (Z)‐3‐hexen‐1‐ol showed a significant and negative correlation with the ‘Green grassy’ attribute, 2‐methylpyrazine showed a significant and negative correlation with the ‘Floral’ attribute, cis‐linalool oxide, trans‐linalool oxide and nerolidol showed a significant and positive correlation with the ‘Woody’ attribute, cis‐6‐nonen‐1‐ol and 2‐methylpyrazine showed a significant and negative correlation with the ’Woody‘ attribute. The primary aim of the current research was (1) to apply descriptive sensory analysis to describe the aroma attributes of different black teas (2) to analyze the typical aroma compounds by GC‐MS and GC‐O; (3) to elucidate the relationship between tea samples, sensory attributes, and aroma‐active compounds by PLSR. A better understanding of this knowledge will be helpful for the improvement of characteristic aroma of different cultivars of congou black teas.